?? ? TRACE ELEMENTS IN INDIGENOUS MEDICINALPLANTs (RHAzYA STRICTA, VINCA ROSEA ANDFAGONIA CRETICA): Short Communication (Biological Sciences - PJSIR, 1999)
belonging to Apocynaecea and Zygophyllaecea families respectively(Hooker 1882) which are grown all over pakistanand have anticancer property (Watt 1890; Chakraborti andMukherji 1968; Siddiqui and Bukhari 1972).